STUDY OF THE IMPACT OF EMOTIONAL INTELLIGENCE OF TEACHERS WORKING IN HIGHER SECONDARY SCHOOLS ON THEIR OCCUPATIONAL STRESS - Sharma, Santosh; Sharaf, Sangeeta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Education is very important for humans. Education is necessary for the development and progress of humans. Through education, a person's attitude changes and personality develops. But human emotions interfere with his work, behavior and education and do not allow us to take the right decision. Whereas emotional intelligence is that understanding which helps us to work well by thinking in every field of life. The proposed research problem is to study the impact of emotional intelligence of teachers working in higher secondary schools on their occupational stress. The need and importance of research in this is profound. How do teachers working in higher secondary schools adjust their occupational stress using their emotional intelligence and how do they control their emotions in the most difficult situations and find a solution to the problem through their emotional intelligence.